Breast Cancer 2022
DOI: 10.36255/exon-publications-breast-cancer-subtypes
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Breast Cancer

Abstract: expression of the following hormone receptors: estrogen (ER), progesterone (PR) and human epidermal growth factor (HER2). Accordingly, the following four subtypes of breast cancer are widely recognized: luminal A, luminal B, HER2-positive, and triple-negative. With the recent advances in cancer research, and an increased molecular understanding of breast cancer, the current clinical model for classification of breast cancer may be benefit from the addition of several molecular markers such as miRNAs (let-7, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…The PR is expressed in more than 50% of ER-positive tumors and rarely in ER-negative BCs. The proliferation marker Ki-67 is low in luminal A, variable in luminal B, and high in HER2+-enriched BCs and TNBCs [ 7 ]. The prevalence of the BC types varies between the studies and was reported between 31–86% for luminal A type, 6–16% luminal B, 2–16% HER2-enriched and 4–26% for triple-negative (TNBC or basal-like) tumors [ 8 ].…”
Section: Types Of Breast Cancer and Metastasismentioning
confidence: 99%
“…The PR is expressed in more than 50% of ER-positive tumors and rarely in ER-negative BCs. The proliferation marker Ki-67 is low in luminal A, variable in luminal B, and high in HER2+-enriched BCs and TNBCs [ 7 ]. The prevalence of the BC types varies between the studies and was reported between 31–86% for luminal A type, 6–16% luminal B, 2–16% HER2-enriched and 4–26% for triple-negative (TNBC or basal-like) tumors [ 8 ].…”
Section: Types Of Breast Cancer and Metastasismentioning
confidence: 99%
“…Breast cancer refers to a heterogeneous group of cancers with different characteristics including histology parameters, the pattern of gene expression, metastatic potential, and prognosis [ 3 ]. Five molecular subtypes of breast cancer are defined: (i) luminal A, (ii) luminal B, (iii) epidermal growth factor receptor-positive (HER2+), (iv) triple-negative breast cancer (TNBC), and (v) seminormal [ 4 ]. Most of the diagnosed breast cancer cases represent the estrogen-receptor-positive (ER+), luminal A subtype (70%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women's cancers, especially breast cancer, are the most heterogeneous and common, can be classified into four distinct subtypes based on the immunohistochemical expression of hormone receptors: progesterone receptor positive (PR+), estrogen receptor-positive (ER+), human epidermal growth factor receptor 2 positive (HER2+) and triple-negative (TNBC) [1]. As the name of triple-negative breast cancer implies, the hormone receptors of all three types are absent in TNBC.…”
Section: Introductionmentioning
confidence: 99%